2022
DOI: 10.3389/fcvm.2022.1009926
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinogen levels in relation to colorectal cancer onset: A nested case-cohort study from the Moli-sani cohort

Abstract: BackgroundPatients with cancer are commonly characterized by abnormalities in laboratory coagulation tests, underlying a subclinical hypercoagulable condition. Due to the involvement of the hemostatic system in cancer patients, some of its biomarkers, such as fibrinogen, could be a useful tool in predicting cancer risk. We performed a case-cohort study to evaluate the relationship among fibrinogen levels and colorectal cancer (CRC).MethodsIn the framework of Moli-sani Study (N = 24,325, enrolled 2005–2010) a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 47 publications
1
3
1
Order By: Relevance
“…This finding supports the chronic low-level inflammation as a latent contributor of cancer development (30,31). A nested case-cohort study indicated that fibrinogen (≥400 mg/dl) was positively correlated with CRC, suggesting that it may be a latent biomarker of CRC and supporting the "common soil" hypothesis (32). Advanced adenoma, a precursor of CRC, also showed an increased risk associated with elevated fibrinogen levels in our study.…”
Section: Discussionsupporting
confidence: 88%
“…This finding supports the chronic low-level inflammation as a latent contributor of cancer development (30,31). A nested case-cohort study indicated that fibrinogen (≥400 mg/dl) was positively correlated with CRC, suggesting that it may be a latent biomarker of CRC and supporting the "common soil" hypothesis (32). Advanced adenoma, a precursor of CRC, also showed an increased risk associated with elevated fibrinogen levels in our study.…”
Section: Discussionsupporting
confidence: 88%
“…14,30,31 In addition, few studies from general adult population reported that high levels of fibrinogen were as-sociated with increased risk of fatal and not fatal colorectal, breast and lung cancers. 13,32 In the present study, no relevant associations were found with cancer mortality in either gender.…”
Section: N O N -C O M M E R C I a L U S E O N L Ycontrasting
confidence: 78%
“…Moreover, the complex cross-talk between the activation of coagulation and inflammation in cancer has received much attention. Abnormal hypercoagulable condition is often observed in most cancer patients (41). FIB is a glycoprotein in coagulation and is synthesized by the hepatocytes.…”
Section: Discussionmentioning
confidence: 99%